Tatalaksana Hipertensi - Salshabilla, Annisa; Pardilawati, Citra Yulianda; Sangging, Putu Ristyaning Ayu; Oktarlina, Rasmi Zakiah (Medula, 2024)
Hypertension is called the "silent killer" because there are no specific symptoms for sufferers and it is the main cause of death throughout the world. Hypertension or high blood pressure is a condition where systolic blood pressure increases ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. According to WHO (World Health Organization), an estimated 1.28 billion adults aged 30-79 years suffer from hypertension worldwide. Riskesdas data for 2018 states that the prevalence of hypertension in Indonesia is 658,201. The pathophysiology of hypertension occurs through the process of forming angiotensin I into angiotensin II by angiotensin I converting enzyme (ACE). Management of hypertension includes non-pharmacological management and pharmacological management. Some non-pharmacological management measures include weight loss, implementing Dietary Approaches to Stop Hypertension (DASH), adopting a low salt diet, consuming potassium supplements, increasing physical activity, and reducing alcohol consumption. Recommended pharmacological therapy in hypertensive patients such as ACEi or ARB with CCB or thiazide/thiazide-like diuretics.